Investigation and damping of electromechanical oscillations for grid integrated micro grid by a novel coordinated governor-fractional power system stabilizer - Nahak, Narayan; Satapathy, Omkar (Energy sources. Part A, Recovery, utilization, and environmental effects, 2025)
Electro mechanical low frequency oscillation generated in a micro-grid (MG) when subjected to uncertain disturbances, and stochastic renewable penetration is more aggravated especially when connected to grid. This needs more investigation for the smooth operation of power system and employment of power electronics-based costly control may not be economic for a MG. Also in the current scenario of deregulated market, more stress is imposed on the optimal use of present resources like mechanical torque control provided by turbine governors. In this work, a synchronous generator(SG)-based grid connected MG with Solar Photo Voltaic (SPV) and wind integration has been investigated for low frequency oscillation pertaining to small signal stability enhancement. A new simple governor (Gov)-Power system stabilizer (PSS), which is GOV-PSS controller has been proposed here with proportional integral derivative (PID), lead-lag and fractional lead-lag PSS actions, which coordinates the governor and PSS for oscillation damping and can be easily implemented. The gains of proposed controller are tuned by a new hybrid differential evolution with improved gray wolf optimizer with a multi objective function. The SPV, wind generations, and reference voltages are randomly varied giving rise to critical oscillatory instability, and proposed optimal controller is implemented to damp these oscillations. The excitation gains are also tuned for all generators subject to each condition such that the tuning of PSS would not adversely influence terminal voltage control. Time and frequency response of the system have been analyzed with 9-bus and 33-bus MG structures employing three generators of 1.32 MVA, 0.91 MVA, and 0.67 MVA. Solar and wind penetrations are executed with the bus connected to 1.32 MVA for 9-bus system and with all generators for 33-bus system. The oscillations due to renewable penetrations are found to be enhanced with reduced synchronous generation contribution. It is observed that properly tuned governor and PSS coordinate each other to enhance stability in proposed controller much effectively in contrast to only governor and PSS actions considered individually. Also turbine governors need not be blocked to damp inter area oscillatory mode, rather their efficacy is much enhanced with proposed control action, and this can be implemented to any SG-based generation including gas, steam, and hydro power-based plants.